Autonomic nervous system influences on qt interval in normal subjects - Magnano, Anthony R; Holleran, Steve; Ramakrishnan, Rajasekhar; Reiffel, James A; Bloomfield, Daniel M (Journal of the American College of Cardiology, 2002)
We sought to determine whether the relationship between heart rate (HR) and QT interval (QT) differs as HR increases in response to exercise, atropine and isoproterenol. Autonomic nervous system influences on repolarization are poorly understood and may complicate the interpretation of QT measurements. Twenty-five normal subjects sequentially underwent graded-intensity bicycle exercise, atropine injection and isoproterenol infusion. Serial 12-lead electrocardiograms were recorded at steady state during each condition and analyzed using interactive computer software. The HR-QT data were modeled linearly and the slopes (quantifying QT adaptation to HR) as well as the QT intervals at 100 beats/min for each intervention were compared by repeated-measures analysis of variance. As HR increased, QT was longer for isoproterenol in comparison to exercise or atropine, which were similar. The HR-QT slope (ms/beats/min) was less steep for isoproterenol (−0.83 ± 0.53) than for atropine (−1.45 ± 0.21) or exercise (−1.37 ± 0.23) (p < 0.0001). In comparison to men, women had more negative HR-QT slopes during all interventions. At 100 beats/min, the QT was 364 ms during isoproterenol, which was significantly longer than that during exercise (330 ms) or atropine (339 ms) (p < 0.0001). Isoproterenol produced a dose-dependent increase in U-wave amplitude that was not observed during exercise or atropine. In comparison to exercise and atropine, isoproterenol is associated with much less QT shortening for a given increase in HR and, therefore, greater absolute QT intervals. Our findings demonstrate that autonomic conditions directly affect the ventricular myocardium of healthy subjects, causing differences in QT that are independent of HR.